Take control of Scrivener 2 - McElhearn, Kirk (Take control., 2011)
You'll learn how to handle each aspect of the flexible Scrivener manuscript-generation process:Set up: Add reference materials to your project for easy access - videos, audio files, PDFs, Web resources, and more. And, if you've already written bits of text, you can import those items too, including OPML outline files (such as from OmniOutliner Pro). Beyond importing from the Finder, you can use Mac OS X Services or Scrivener's handy Scratch Pad panel. Or, you can use the Import and Split feature to import a long document into multiple chapters or segments in Scrivener.Organize: Use the Outline.